Dead again [videorecording (DVD)] - Branagh, Kenneth; Frank, Scott, 1960-; Leonetti, Matthew F., 1941-; Thompson, Emma (Paramount, 2006)
An L.A. detective is perplexed when he is hired to help a beautiful amnesia victim who is tormented by nightmares, which may lie in a past-life connection to a pianist murdered by her husband.